Prevalence and associated factors of diarrhea among under-five children in Debre Berhan town, Ethiopia 2018: a cross sectional study - Sisay Shine (BMC Infectious Diseases, 2020)
Abstract Background Diarrhea is responsible for 525,000 children under-five deaths and 1.7 billion cases globally and is the second leading cause of death among children under-five every year. It is a major public health problem in low income countries like Ethiopia. The main aim of this study was to assess the prevalence of diarrhea and associated risk factors among children under-five in Debre Berhan Town, Ethiopia. Methods A community-based cross-sectional study was conducted in 420 parent or caretaker/children pairs in Debre Berhan town between 13 and 18 April 2018. A multi-stage sampling strategy was used to select the study participants. Data were collected using pre-tested and structured questionnaires. Data were entered in Epi-info computer software version 3.5.1 and exported to SPSS Window Version-16 for analysis. Adjusted odds ratio with 95% confidence intervals were used to assess the level of significance. Results The two week prevalence of diarrhea among children under-five was 16.4% (69/351). Children aged 7–11 months (adjusted odds ratio (AOR): 4.2, 95% confidence interval (CI): 1.2–15.3), being the second-born child (AOR: 3.9, 95%CI: 1.8–8.5), not vaccinated against rotavirus (AOR: 10.3, 95%CI: 3.2–91.3) and feeding children by hand (AOR: 2.5, 95%CI: 1.1–6.1) were significant predictors of diarrhea. Conclusions This study revealed that the two weeks period prevalence of diarrhea among children under-five years was 16.4%. Education programs on the importance of vaccination against rotavirus, increasing breast feeding frequency with complementary food after six months and the critical points of hand washing are recommended.